Analisis Etika Bisnis Islam dalam Persaingan Usaha Pabbagang di Desa Pallemeang Kabupaten Pinrang - Rosmaya Rosmaya; Muhammad Ali Rusdi Bedong; Muhammad Kamal Zubair; Wahidin Wahidin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
One form of business competition in Pallameang Village is the competition carried out by pabbagang. There are two dominant types of pabbagang in Pallameang Village, namely pabbagang rambo (boat chart) and pabbagang tancap (tancap chart). Both have their own characteristics as well as their own advantages. Pabbagang rambo (boat chart) more often uses the medium of boats in its operationals. Meanwhile, the pabbagang tancap (bamboo chart), is an arrangement series of bamboo in a quadrangle form that is plugged and it stands firmly on the water, where in the middle of bamboo arrangement a net is installed. The results of the study showed that the competition between fishermen in Pallameang Village is by catching fish through pabbagang tancap and pabbagang rambo. There were business competitions in different types of use of charts affects costs, as well as the results they obtain, as well as the competition that occurs on fishermen of Pallameang Village in accordance with the existing Islamic business ethics, this is based on the principles in Islamic business ethics that have been applied by pabbagang rambo and pabbagang tancap in Pallameang Village. These, based on the principles in Islamic business ethics, namely the concepts of tauhid, mandate and justice.